Urgency Of The Balance Of Knowledge And Characteristics Education In Forming The Character Of Children In Pajarakan Gading Probolinggo - Zahida I'tisoma Billah; Moh. Abd. Rahman (IAI Darussalam, 2023)
This service aims to: (1) Find out how far the balance of knowledge and character education for children in Wangkal village is (2) Cooperate with formal and non-formal educational institutions in the local village (3) Invite parents to pay more attention to behavior children's morals when outside school (4) Providing advice or input to figures and parents as the first teacher to take the right steps in order to improve the balance of knowledge gained and morals as a practice in life. This PKM takes place in Krajan Hamlet, Wangkal Village, Gading District, Probolinggo Regency, using the ABCD method with a community development approach. Starting from the Discovery, Dream, Design, to Destiny stages.Moral education in schools is not enough to provide learning about ethics and manners in just a few hours a day. In conclusion, it is parents who should be the first teacher in shaping the child's personality, mindset, attitude patterns and lifestyle. But what happens a lot is that parents hand over their children's moral/moral education to the school at random. Keywords: Urgency, Manners, Character